2021
DOI: 10.1177/10732748211055262
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends of Breast Cancer in Southern Ethiopia: A Seven-Year Retrospective Review

Abstract: Introduction African women are affected by cancer at an early age of their productivity. However, the exact prevalence and incidence of cancer, including breast cancer is not known in most sub-Saharan African countries, including Ethiopia because of lack of well-established cancer registry. This study aims to assess the epidemiology of breast cancer at Hawassa University Comprehensive Specialized Hospital (HUCSH), the biggest referral hospital with cancer treatment center serving the southern part of the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…The median and peak ages have also been reported in some studies. The peak age of incidence of 47.8%, 52.5%, 57.4%, 57.5% and 57.9% between the 3rd and 5 th decades among patients in Rwanda, Lagos-Nigeria, Southern Ethiopia, Central African Republic and Northwest Amhara regions of Ethiopia, respectively [9,17,[19][20][21]. Similar report was observed among breast cancer patients in Adis Ababa Ethiopia with 63.1% at the same peak range [22].…”
Section: The Distribution Of Breast Cancer In Sub-saharan Africasupporting
confidence: 73%
See 3 more Smart Citations
“…The median and peak ages have also been reported in some studies. The peak age of incidence of 47.8%, 52.5%, 57.4%, 57.5% and 57.9% between the 3rd and 5 th decades among patients in Rwanda, Lagos-Nigeria, Southern Ethiopia, Central African Republic and Northwest Amhara regions of Ethiopia, respectively [9,17,[19][20][21]. Similar report was observed among breast cancer patients in Adis Ababa Ethiopia with 63.1% at the same peak range [22].…”
Section: The Distribution Of Breast Cancer In Sub-saharan Africasupporting
confidence: 73%
“…Almost two-thirds of breast cancer patients are below 50 years old in Burkina Faso [23]. Gabretsadik A et al, in a seven-year (2013-2019) review, reported a median age of 38 years among patients in Southern Ethiopia [21]. Ouedraogo [9,18,19,23].…”
Section: The Distribution Of Breast Cancer In Sub-saharan Africamentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 88.88% of breast cancers were diagnosed with an advanced clinical stage (III and IV). The observation is the same in several other developing countries where 65% to 90% of breast cancers are seen in consultation at a late stage [18] [23] [26] [27] [28] [29] [30]. In developed countries, such Australia and England, 55.9% and 56.8% of breast cancers are diagnosed at a localized stage respectively [31] [32].…”
Section: Diagnostic Aspects Of Breast Cancermentioning
confidence: 54%